2021
DOI: 10.1101/2021.02.17.20246504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fat-enlarged Axillary Lymph Nodes are Associated with Node-Positive Breast Cancer in Obese Patients

Abstract: Purpose Obesity-associated fat infiltration of organ systems is accompanied by organ dysfunction and poor cancer outcomes. Obese women demonstrate variable degrees of fat infiltration of axillary lymph nodes (LNs), and they are at increased risk for node-positive breast cancer. However, the relationship between enlarged axillary nodes and axillary metastases has not been investigated. The purpose of this study is to evaluate the association between axillary metastases and fat-enlarged axillary nodes visualize… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Prior studies have shown that non-metastatic axillary nodes may be enlarged by excess hilar fat deposition and are more commonly seen in women with obesity 17,18 . Fat-enlarged non-metastatic axillary lymph nodes identified on mammography and breast MRI are associated with a high risk of axillary metastasis in obese patients with invasive breast cancer, and this association is maintained when adjusting for patient and tumor characteristics 19 . Our hypothesize is that, hyperadiposity and micro-immune dysregulation may also occur in axillary nodal adiposity, creating a pre-metastatic niche for nodal metastases in women with invasive breast cancer.…”
Section: Introductionmentioning
confidence: 87%
“…Prior studies have shown that non-metastatic axillary nodes may be enlarged by excess hilar fat deposition and are more commonly seen in women with obesity 17,18 . Fat-enlarged non-metastatic axillary lymph nodes identified on mammography and breast MRI are associated with a high risk of axillary metastasis in obese patients with invasive breast cancer, and this association is maintained when adjusting for patient and tumor characteristics 19 . Our hypothesize is that, hyperadiposity and micro-immune dysregulation may also occur in axillary nodal adiposity, creating a pre-metastatic niche for nodal metastases in women with invasive breast cancer.…”
Section: Introductionmentioning
confidence: 87%